KOMUNIKASI PEMBINAAN USIA DINI DI SEKOLAH SEPAK BOLA ARIS INDARTO FOOTBALL ACADEMY - Corrina Kayla Shatiani; Flora Meliana Siahaan (STKIP Subang, 2026)
This research was motivated by the importance of communication in the early-age coaching process at a football school. Effective communication functions not only as a means of delivering training instructions but also plays an essential role in building motivation, instilling discipline, shaping character, and establishing positive relationships between coaches and students. Aris Indarto Football Academy (AIFA) implements a coaching concept that emphasizes the learning process, making communication one of the key factors in achieving successful player development. The purpose of this study is to identify and describe the communication process used in early-age coaching at Aris Indarto Football Academy and to determine the factors influencing the effectiveness of communication between coaches and students. This research employed a constructivist paradigm with a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation. The research informants consisted of Coach Aris Indarto as the key informant and one student of Aris Indarto Football Academy as the supporting informant. Data were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that the coaching communication process at Aris Indarto Football Academy is conducted through interpersonal, two-way communication, including pre-training briefings, direct guidance during training sessions, and evaluations after training. The coach uses simple and understandable language, demonstrates techniques directly, provides motivation and constructive feedback, and develops close relationships with students through personal approaches. Based on Joseph A. DeVito's Interpersonal Communication Theory, the communication practiced fulfills the characteristics of openness, empathy, supportiveness, positiveness, and equality. This communication has a positive impact on students' understanding, self-confidence, discipline, teamwork, responsibility, and character development. Factors influencing communication effectiveness include the use of simple language, two-way communication, direct demonstrations, close relationships between coach and students, and regular evaluations. Meanwhile, communication barriers include differences in students' personalities, lack of concentration during training, reluctance to ask questions, and varying levels of understanding. These obstacles are addressed through personal interpersonal communication, enabling students to express their difficulties more comfortably. In conclusion, interpersonal communication plays a significant role in the success of early-age coaching at Aris Indarto Football Academy. Communication that is open, empathetic, supportive, and respectful creates an effective coaching process that not only improves students' football skills but also develops their character and mental readiness in accordance with the academy's coaching objectives.